The Role of NRF2 in Obesity-Associated Cardiovascular Risk Factors - Jorge Gutiérrez-Cuevas; Marina Galicia-Moreno; Hugo Christian Monroy-Ramírez; Ana Sandoval-Rodriguez; Jesús García-Bañuelos; Arturo Santos; Juan Armendariz-Borunda (Antioxidants, 2022)
The raising prevalence of obesity is associated with an increased risk for cardiovascular diseases (CVDs), particularly coronary artery disease (CAD), and heart failure, including atrial fibrillation, ventricular arrhythmias and sudden death. Obesity contributes directly to incident cardiovascular risk factors, including hyperglycemia or diabetes, dyslipidemia, and hypertension, which are involved in atherosclerosis, including structural and functional cardiac alterations, which lead to cardiac dysfunction. CVDs are the main cause of morbidity and mortality worldwide. In obesity, visceral and epicardial adipose tissue generate inflammatory cytokines and reactive oxygen species (ROS), which induce oxidative stress and contribute to the pathogenesis of CVDs. Nuclear factor erythroid 2-related factor 2 (NRF2; encoded by Nfe2l2 gene) protects against oxidative stress and electrophilic stress. NRF2 participates in the regulation of cell inflammatory responses and lipid metabolism, including the expression of over 1000 genes in the cell under normal and stressed environments. NRF2 is downregulated in diabetes, hypertension, and inflammation. Nfe2l2 knockout mice develop structural and functional cardiac alterations, and NRF2 deficiency in macrophages increases atherosclerosis. Given the endothelial and cardiac protective effects of NRF2 in experimental models, its activation using pharmacological or natural products is a promising therapeutic approach for obesity and CVDs. This review provides a comprehensive summary of the current knowledge on the role of NRF2 in obesity-associated cardiovascular risk factors.